Keanekabahasaan dalam Novel Orang-Orang Oetimu Karya Felix K. Nesi (Kajian Sosiolinguistik) - Sri Wahyuni; Wahyu Widayati (Madah: Jurnal Bahasa dan Sastra, 2022)
The highlight of this research is finding the diversity in the novel Orang-Orang Oetimu by Felix K. Nesi. The analysis of the study of diversity in the Orang-Orang Oetimu novel is actually an attempt to find a picture of diversity in literary works. Diversity can be interpreted as the diversity of languages ​​or the kinds of languages ​​used in a particular area. In the analysis, the researcher uses sociolinguistics as a knife to express diversity. Qualitative descriptive method was chosen as the research method with the object of study in the form of the novel Orang-Orang Oetimu by Felix K. Nesi. The data collection method used literature study with analytical descriptive technique as a data analysis technique. The findings of the researcher show that the Oetimu people are multilingual, including: (i) the Uab Meto language, (ii) the Kupang language, (iii) the Tetun language, and (iv) the Timorese Malay. The findings of the analysis confirm that multilingualism in an area is influenced by social factors, such as: colonization of foreign nations, geographical location, racial equality, group agreement, and so on.